Optimal. Leaf size=19 \[ \frac {1}{2} e^{-6-x} \left (-10+e-x^2\right ) \]
________________________________________________________________________________________
Rubi [A] time = 0.07, antiderivative size = 31, normalized size of antiderivative = 1.63, number of steps used = 9, number of rules used = 4, integrand size = 22, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.182, Rules used = {12, 2196, 2194, 2176} \begin {gather*} -\frac {1}{2} e^{-x-6} x^2-\frac {1}{2} (10-e) e^{-x-6} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 12
Rule 2176
Rule 2194
Rule 2196
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\frac {1}{2} \int e^{-6-x} \left (10-e-2 x+x^2\right ) \, dx\\ &=\frac {1}{2} \int \left (10 \left (1-\frac {e}{10}\right ) e^{-6-x}-2 e^{-6-x} x+e^{-6-x} x^2\right ) \, dx\\ &=\frac {1}{2} \int e^{-6-x} x^2 \, dx+\frac {1}{2} (10-e) \int e^{-6-x} \, dx-\int e^{-6-x} x \, dx\\ &=-\frac {1}{2} (10-e) e^{-6-x}+e^{-6-x} x-\frac {1}{2} e^{-6-x} x^2-\int e^{-6-x} \, dx+\int e^{-6-x} x \, dx\\ &=e^{-6-x}-\frac {1}{2} (10-e) e^{-6-x}-\frac {1}{2} e^{-6-x} x^2+\int e^{-6-x} \, dx\\ &=-\frac {1}{2} (10-e) e^{-6-x}-\frac {1}{2} e^{-6-x} x^2\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.01, size = 19, normalized size = 1.00 \begin {gather*} \frac {1}{2} e^{-6-x} \left (-10+e-x^2\right ) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.62, size = 17, normalized size = 0.89 \begin {gather*} -\frac {1}{2} \, {\left (x^{2} - e + 10\right )} e^{\left (-x - 6\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.16, size = 22, normalized size = 1.16 \begin {gather*} -\frac {1}{2} \, {\left (x^{2} + 10\right )} e^{\left (-x - 6\right )} + \frac {1}{2} \, e^{\left (-x - 5\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.05, size = 18, normalized size = 0.95
method | result | size |
risch | \(\frac {\left ({\mathrm e}-x^{2}-10\right ) {\mathrm e}^{-x -6}}{2}\) | \(18\) |
gosper | \(\frac {{\mathrm e}^{-3} \left ({\mathrm e}-x^{2}-10\right ) {\mathrm e}^{-3-x}}{2}\) | \(22\) |
norman | \(\left (-\frac {x^{2} {\mathrm e}^{-3}}{2}+\frac {{\mathrm e}^{-3} \left ({\mathrm e}-10\right )}{2}\right ) {\mathrm e}^{-3-x}\) | \(28\) |
derivativedivides | \(\frac {{\mathrm e}^{-3} \left (-{\mathrm e}^{-3-x} \left (3+x \right )^{2}+6 \,{\mathrm e}^{-3-x} \left (3+x \right )-19 \,{\mathrm e}^{-3-x}+{\mathrm e}^{-3-x} {\mathrm e}\right )}{2}\) | \(49\) |
default | \(\frac {{\mathrm e}^{-3} \left (-{\mathrm e}^{-3-x} \left (3+x \right )^{2}+6 \,{\mathrm e}^{-3-x} \left (3+x \right )-19 \,{\mathrm e}^{-3-x}+{\mathrm e}^{-3-x} {\mathrm e}\right )}{2}\) | \(49\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [B] time = 0.43, size = 43, normalized size = 2.26 \begin {gather*} -\frac {1}{2} \, {\left (x^{2} + 2 \, x + 2\right )} e^{\left (-x - 6\right )} + {\left (x + 1\right )} e^{\left (-x - 6\right )} + \frac {1}{2} \, e^{\left (-x - 5\right )} - 5 \, e^{\left (-x - 6\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 0.07, size = 19, normalized size = 1.00 \begin {gather*} -{\mathrm {e}}^{-x-6}\,\left (\frac {x^2}{2}-\frac {\mathrm {e}}{2}+5\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.11, size = 19, normalized size = 1.00 \begin {gather*} \frac {\left (- x^{2} - 10 + e\right ) e^{- x - 3}}{2 e^{3}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________